Group Activity Therapy-Based Tai Chi Exercises on Improving Muscle Strength in Older Adults - Zuan Nun Alea Syavinka; Kartinah Kartinah (Sarana Ilmu Indonesia (salnesia), 2026)
Older adults experience a decline in muscle strength due to the aging process, which leads to limitations in physical activity and an increased risk of dependency. Among the interventions that can be implemented is Tai Chi exercise based on Group Activity Therapy (GAT), which involves physical exercises with slow, controlled movements performed in a group setting to improve physical function and motivation in older adults. This study aimed to determine the effectiveness of Group Activity Therapy (GAT)-based Tai Chi exercises on improving muscle strength in older adults before and after the intervention. This study employed a One-Group Pre-Post Test Design involving 10 older adults at the Tresna Werdha Budi Luhur Social Service Center in Yogyakarta. Muscle strength assessments were conducted before and after the intervention using a manual muscle strength test. The data were analyzed using the Wilcoxon Signed-Rank Test, and the results showed a p-value of 0.003, which is less than 0.05 (p = 0.003 < 0.05). The results indicated a significant difference in muscle strength before and after the intervention, suggesting that group activity therapy-based Tai Chi exercises had a significant effect on improving muscle strength in older adults. Therefore, this intervention may serve as an effective non-pharmacological therapy to support independence and improve muscle strength in older adults.